Impact of an Antibiotic Stewardship Program in Long-term Care Facilities: A Nursing Home Network Experience. (4th October 2017) - Romero, Fabian Andres; Mathews, Evette; Flores, Ara; Seo, Susan
Abstract: Background: Antibiotic stewardship program (ASP) implementation is paramount across the healthcare spectrum. Nursing homes represent a challenge due to limited resources, complexity of medical conditions, and less controlled environments. National statistics on ASP for long-term care facilities (LTCF) are sparse. Methods: A pilot ASP was launched in August 2016 at a 270-bed nursing home with a 50-bed chronic ventilator-dependent unit. The program entailed a bundle of interventions including leadership engagement, a tracking and reporting system for intravenous antibiotics, education for caregivers, Infectious Disease (ID) consultant availability, and implementation of nursing protocols. Data were collected from pharmacy and medical records between January 2016 and March 2017, establishing pre-intervention and post-intervention periods. Collected data included days of therapy (DOT), antibiotic costs, resident-days, hospital transfers, and Clostridium difficile infection (CDI) rates. Variables were adjusted to 1, 000 resident-days (RD) and findings between periods were compared by Mann–Whitney U test. Results: A total of 47, 423 resident-days and 1, 959 DOT were analyzed for this study. Antibiotic use decreased from 54.5 DOT/1000 RD pre-intervention to 27.6 DOT/1000 RD post-intervention ( P  = 0.017). Antibiotic costs were reduced from a monthly median of US $17, 113 to US $7, 073 but was not statistically significant ( P  = 0.39). Analysis stratified by individual antibiotic was done for the five most commonly used antibiotics and found statistically significant reduction in vancomycin use (14.4 vs. 6.5; P  = 0.023). Reduction was also found for cefepime/ceftazidime (6.9 vs. 1.3; P  = 0.07), ertapenem (6.8 vs. 3.6; P  = 0.45), and piperacillin/tazobactam (1.8 vs. 0.6; P  = 0.38). Meropenem use increased (1.3 vs. 3.2; P  = 0.042). Hospital transfers slightly trended up (6.73 vs. 7.77; P  = 0.065), and there was no change in CDI (1.1 s 0.94; P  = 0.32). Conclusion: A bundle of standardized interventions tailored for LTCF can achieve successful reduction of antibiotic utilization and costs. Subsequent studies are needed to further determine the impact on clinical outcomes such as transfers to hospitals and CDI in these settings. Disclosures: All authors: No reported disclosures.